Ethnomathematics Based Mpa’a Gopa Game Learning Media to Improve Mathematical Literacy and Cultural Character - Husnul Khatimah; Nunung Fatimah; M. Abid Saputra; Anggih Tri Cahyadi; Nanang Diana; Nur Afni (Prima: Jurnal Pendidikan Matematika, 2026)
Mathematics plays a crucial role in developing students’ problem-solving, reasoning, and communication skills, yet many learners in Indonesia, particularly in Bima Regency, continue to face challenges with low mathematical literacy. This issue is often linked to limited engagement in the classroom and the dominance of teacher-centered approaches, which hinder students from bridging conceptual understanding with real-world applications. To address this gap, ethnomathematics-based learning offers an innovative approach by contextualizing mathematical concepts through local culture. This study aimed to develop and evaluate mathematics learning media based on the traditional game Mpa’a Gopa, integrating cultural identity and mathematical concepts to enhance students’ literacy and character. The research adopted the 4D development model (Define, Design, Develop, Disseminate) and was conducted with 20 fourth-grade students at SD Negeri 2 Maria, Bima Regency. Data were collected through expert validation sheets, student questionnaires, teacher and student observation sheets, and pretest–posttest assessments to measure validity, practicality, and effectiveness. The results indicated that the developed media met all quality standards; expert validation rated the product from good to very good, while student responses were overwhelmingly positive, with 99% agreeing that the media improved motivation and comprehension. Teacher and student observations further confirmed smooth classroom implementation. The average student score increased from 66.19 (pretest) to 82.23 (posttest), with mastery levels rising from 52.38% to 90.47%, and the N-Gain score of 0.60 categorized as medium. In conclusion, integrating ethnomathematics-based traditional games into mathematics learning not only strengthens mathematical literacy and student motivation but also promotes cultural awareness, making Mpa’a Gopa a meaningful instructional tool and a strategy for cultural preservation